2015
DOI: 10.1039/c4ta06943a
|View full text |Cite
|
Sign up to set email alerts
|

Phase-controlled synthesis of polymorphic MnO2 structures for electrochemical energy storage

Abstract: Manganese dioxide (MnO 2 ) with a-, b-and d-type structures was controllably synthesized by hydrothermal treatment of an acidic solution of KMnO 4 containing different concentrations of ions at 160 C. The effects of metallic cations, H + and anions on the structures and morphologies of MnO 2 were investigated systematically. The experimental results indicated that cations played a significant part in the formation of MnO 2 with different structures. When K + ions were in competition with H + ions in solution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
97
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(104 citation statements)
references
References 34 publications
7
97
0
Order By: Relevance
“…The use of pseudocapacitive materials, such as transition metal oxides and conducting polymers [12][13][14][15], instead of carbon based materials, leads to enhanced energy density without significant loss of power density. This enhancement results from the additive effect of fast superficial redox reactions and electric double layer formation at the electrode/electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%
“…The use of pseudocapacitive materials, such as transition metal oxides and conducting polymers [12][13][14][15], instead of carbon based materials, leads to enhanced energy density without significant loss of power density. This enhancement results from the additive effect of fast superficial redox reactions and electric double layer formation at the electrode/electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the morphologies of α-MnO 2 samples in our work were different from the nanospheres/nanosheets or nanorods reported in M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT the references [34,35].…”
Section: Introductionmentioning
confidence: 51%
“…Cheng et al [34] prepared α-MnO 2 nanospheres/nanosheets in KMnO 4 -H 2 SO 4 reaction system at 160 °C for 10h. Yin et al [35] successfully synthesized different MnO 2 structures by controlling the concentration of K + and H + in KMnO 4 -HNO 3 reaction system at 160 °C for 24h. The results indicated that β-MnO 2 particles were obtained when H + ions was more than K + ions; and α-MnO 2 nanorods were formed when K + ions was more than H + ions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, manganese dioxide (MnO 2 ) has attracted considerable attention because of their catalysis, molecular sieves and electrodes in rechargeable batteries, owing to their excellent electrochemical performance, low cost, nonpoisonous nature, environmental friendliness, and convenient preparation (Athouël, Moser, Dugas, Crosnier, Bélanger & Brousse, 2008;Qu et al, 2009;Tang, Meng & Huang, 2014;Zhang et al, 2012;Zhang et al, 2011). The MnO 2 has many polymorphic forms (α, β, γ and δ) (Kim et al, 2007;Yin, Zhang, Jiang, Qu & Wu, 2015;Zeng, Wang, Yang & Zhang, 2010;Zhu, Li, Deng & Liu, 2010). The α-MnO 2 has a hollandite-type structure including double chains of [MnO 6 ] octahedra forming 2 × 2 tunnels (Li, Pan, Chen & Li, 2007;Su, Ahn & Wang, 2013).…”
Section: Introductionmentioning
confidence: 99%